Forensic analytics : methods and techniques for forensic accounting investigations - Nigrini, Mark J. (Mark John) (Hoboken, N.J. : Wiley, 2011)
"The book will review and discuss (with Access and Excel examples) the methods and techniques that investigators can use to uncover anomalies in corporate and public sector data. These anomalies would include errors, biases, duplicates, number rounding, and omissions. The focus will be the detection of fraud, intentional errors, and unintentional errors using data analytics. Despite the quantitative and computing bias, the book will still be interesting to read with interesting vignettes and illustrations. Most chapters will be understandable by accountants and auditors that usually are lacking in the rigors of mathematics and statistics. The data interrogation methods are based on (a) known statistical techniques, and (b) the author's own published research in the field"--
Includes bibliographical references (p. 455- 458) and index.
Keywords: Forensic accounting; Fraud; Misleading financial statements